2001
DOI: 10.1017/s1462399401002812
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant viral hepatitis: molecular and cellular basis, and clinical implications

Abstract: Fulminant viral hepatitis: molecular and cellular basis, and clinical implications 2 expert reviews in molecular medicine Accession information: (01)00281-2a.pdf (short code: txt001glt);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 90 publications
0
38
0
Order By: Relevance
“…MHV-3, a positive-strand RNA virus of the Coronaviridae family, produces a strain-dependent spectrum of liver diseases and immune responses [Ding et al, 1997;Ning et al, 1998Ning et al, , 1999Liu et al, 2001]. STAT1 a is reported to be essential to IFN-g and IFN-a regulated gene expression, while STAT1 b, an alternate spliceform, mediates only IFN-a-dependent gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…MHV-3, a positive-strand RNA virus of the Coronaviridae family, produces a strain-dependent spectrum of liver diseases and immune responses [Ding et al, 1997;Ning et al, 1998Ning et al, , 1999Liu et al, 2001]. STAT1 a is reported to be essential to IFN-g and IFN-a regulated gene expression, while STAT1 b, an alternate spliceform, mediates only IFN-a-dependent gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…HBV infection is the leading cause of severe viral hepatitis in developing countries (1)(2)(3)(4)(5). The host immune response to virus plays a critical role in the pathogenesis of HBV infection (16,17), whereas the HBV Ag-specific CTL is an critical determinant of viral clearance (18,19) and hepatocyte damage in FHF (2, 6).…”
Section: Discussionmentioning
confidence: 99%
“…Fulminant hepatic failure (FHF) and ACLF because of hepatitis B virus (HBV) infection are the most common severe diseases requiring immediate hospitalization in China and many other Asian countries (1)(2)(3)(4)(5). The immunological mechanisms of virus-induced hepatic failure are still not fully defined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that the fibrinogen-like protein-2 (fgl2) prothrombinase expressed by activated macrophages (Kupper cells) plays a crucial role in the pathogenesis of AHF induced by murine hepatitis virus strain 3 (MHV-3) or HBV (Han et al, 2008;Marsden et al, 2003;Ning et al, 1998;Zhu et al, 2005). However, the infiltration of hepatic inflammatory cells should also be noted as another important pathological feature of this disease (Liu et al, 2001). Substantial accumulated inflammatory cells can not only secrete large amount of inflammatory mediators, causing deterioration of the liver microenvironment, but can also directly induce hepatocyte apoptosis and necrosis.…”
Section: Introductionmentioning
confidence: 99%